ABO blood group and ischaemic heart disease in British men. Issue 6741 (30th June 1990) - Whincup, P H; Cook, D G; Phillips, A N; Shaper, A G
Abstract : OBJECTIVE–To establish whether ABO blood group is related to ischaemic heart disease on an individual and geographic basis in Britain. DESIGN–Prospective study of 7662 men with known ABO blood group selected from age-sex registers in general practices in 24 British towns. MEASUREMENTS–ABO blood group, standard cardiovascular risk factors, social class, and presence or absence of ischaemic heart disease determined at entry to study. END POINTS–Eight year follow up of fatal and nonfatal ischaemic heart disease events achieved for 99% of study population. RESULTS–Towns with a higher prevalence of blood group O had higher incidences of ischaemic heart disease. In individual subjects, however, the incidence of ischaemic heart disease was higher in those with group A than in those with other blood groups (relative risk 1.21, 95% confidence limits 1.01 to 1.46). Total serum cholesterol concentration was slightly higher in subjects of blood group A. No other cardiovascular risk factor (including social class) was related to blood group. CONCLUSIONS–Blood group A is related to the incidence of ischaemic heart disease in individual subjects. Geographic differences in the distribution of ABO blood groups do not explain geographic variation in rates of ischaemic heart disease in Britain. The findings do not support the view that ABO blood group and social class are related.